Global, regional, and national burden of opioid use disorder from 1990 to 2021: a statistical analysis of incidence, mortality, and disability-adjusted life years - Mingxing Fang; Qi Zhang; Jibin Peng; Wenwen Yao; Wenming Feng; Xinan Wan (BMC Public Health)
Abstract Background Opioid use disorder (OUD) present significant health challenges globally, especially among adolescents and young adults. This study leverages the Global Burden of Disease (GBD) Study 2021 to assess the burden of OUD from 1990 to 2021. Methods The incidence, mortality, and disability-adjusted life years (DALYs) of OUD from 1990 to 2021 were extracted from the GBD Study 2021 website. The slope index of inequality (SII) and concentration index of inequality (CII) were used to quantify the inequality of OUD burden across countries. We employed frontier analysis to quantify the gap between a country’s or territory's current burden and its potential minimum burden. Results Globally, in 2021, the number of new cases, deaths, and the DALYs of OUD were 1942.52 thousand [95% uncertainty interval (UI): 1643.34, 2328.36], 99.55 thousand (95% UI: 92.94, 108.04), and 11,218.51 thousand (95% UI: 9188.65, 13,159.55), respectively. The age-standardized rates (ASRs) of incidence, mortality, and DALYs of OUD were 24.54 per 100,000 population (95% UI: 20.74, 29.48), 1.19 per 100,000 population (95% UI: 1.12, 1.29), and 137.15 per 100,000 population (95% UI: 112.29, 161.39), respectively. At the regional level, high-income North America had the most severe burden of OUD. The peak OUD incidence occurred in both males and females aged 20–24 years, and the peak OUD-related mortality occurred in males aged 30–44 years and females aged 30–59 years. Countries with higher SDIs have a heavier burden of OUD, and this trend continues to intensify. Countries with higher SDIs often have greater potential to reduce the burden of OUD. Conclusionq OUD remains an important contributor to the burden of disease and is concentrated mainly among young people, emphasizing the urgency of addressing this public health challenge.